2015
DOI: 10.1149/06917.1179ecst
|View full text |Cite
|
Sign up to set email alerts
|

Indium Tin Oxide as Catalyst Support for PEM Fuel Cell: RDE and MEA Performance

Abstract: High surface area indium tin oxide (ITO) catalyst support materials were synthesized by using co-precipitation method to get uniform and small particle size. Colloidal deposition was used to deposit platinum onto the ITO support. The ITO support demonstrated exceptional electrochemical stability in RDE tests with less than 10% double layer pseudo capacitance loss compared with a 270% change for Vulcan XC-72R carbon under the standard support stability protocol (start-stop). 40%Pt/ITO catalyst showed higher dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
3
1
Order By: Relevance
“…Figure 5 shows the results for the deconvolution of the In3d 5/2 peaks. The first peak, peak 1 at 445.6 eV corresponds to the indium peak corresponding to the ITO structure(In-O, structural O) whereas the second peak, peak 2 at 446.6eV is due to the presence of indium peak corresponding to the indium hydroxide structure (In-OH, structural OH) (Wang et al, 2015). These results are in contradiction with earlier results wherein only one peak was reported for a similar catalyst (Zhao et al, 2015).…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…Figure 5 shows the results for the deconvolution of the In3d 5/2 peaks. The first peak, peak 1 at 445.6 eV corresponds to the indium peak corresponding to the ITO structure(In-O, structural O) whereas the second peak, peak 2 at 446.6eV is due to the presence of indium peak corresponding to the indium hydroxide structure (In-OH, structural OH) (Wang et al, 2015). These results are in contradiction with earlier results wherein only one peak was reported for a similar catalyst (Zhao et al, 2015).…”
Section: Resultscontrasting
confidence: 91%
“…Upon use in the cathode and anode, the O1s binding energy increased to 530.76 and 530.69 eV, respectively. Peak deconvolution of the O1s peaks was performed by assuming the presence of three overlapping peaks (see Figure 4): 1) peak 1 at 529.9 eV, resultant from the oxide in ITO; 2) peak 2 at 530.56 eV, associated with the presence of hydroxide groups in the catalysts surface; and 3) peak 3 at 533.79 eV, related to the presence of oxygen vacancies in the oxide (Wang et al, 2015). We estimated (with an error limit of ±5%) that the oxygen vacancies were 7.5%, 16.3% and 21.6%, for the control, cathode-tested and anode-tested electrocatalysts, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The durability of indium tin oxide under PEMFC conditions was examined in further studies. Wang et al 61 investigated Pt on very similar materials like in this work. Pt on 22 nm ITO particles (here, 23 nm ITO particles from XRD) and Pt supported on Vulcan XC72R (here, the same carbon black type) were compared.…”
Section: Resultsmentioning
confidence: 93%
“…For all the materials prepared we observed that some Pt atoms dispersed on the surface support although, the presence of agglomerated nanoparticles was a majority. Literature describes that commercial ITO has very low area and large distribution in particles size, it is very difficult to get well‐dispersed and uniform Pt‐catalysed ITO support .…”
Section: Methodsmentioning
confidence: 99%